REDUCING THE SEVERITY OF RENAL GRAFT ISCHEMIC AND REPERFUSION INJURY WITH COUPLED PLASMA FILTRATION AND ADSORPTION - A. V. Vatazin; A. B. Zulkarnaev; N. L. Shakhov; R. O. Kantaria; A. P. Faenko; M. Krstich; L. V. Belskich (Вестник трансплантологии и искусственных органов, 2016)
Aim: to evaluate the effectiveness of coupled plasma filtration and adsorption (CPFA) in reducing the severity of the renal graft ischemic and reperfusion injury. Materials and methods: shortand long-term results of renal transplantation in 33 pairs of recipients were analyzed. The patients were divided into two groups: in 33 recipients of the study group we performed CPFA in the early postoperative period. In the comparison group in 33 recipients with paired grafts CPFA was not performed. Results. The proportion of patients with good initial and delayed graft functions in the two groups was the same. In patients with delayed graft function from the study group a significantly greater rate of creatinine and urea decrease and glomerular filtration rate (GFR) increase than in patients of the comparison group were observed. Among patients with good initial graft function the differences between the groups were not significant. We have also analyzed long-term results of the transplantations: patients who received CPFA in the early postoperative period had lower levels of creatinine, urea and daily proteinuria and higher GFR in 1 year time. Thus, as a result of CPFA in the early postoperative period the improvement of graft function and graft survival prognosis can be expected in the long-term.